Characterization of induced metal responses of bacteria isolates from active non-sanitary landfill in Malaysia. (April 2017) - Jayanthi, B.; Emenike, C.U.; Auta, S.H.; Agamuthu, P.; Fauziah, S.H.
Abstract: Microorganisms have specific genetic mechanisms towards their resistance to heavy metals, and may exhibit tolerance by immobilizing metal on cell surfaces or transforming them into less toxic forms. Unfortunately, selecting microbes that are metal-specific is a problem in remediation processes, and require identification of a process/strategy for evaluating metal interaction and bioreduction potential of microbial species before utilization for biodegradation/reduction in polluted soils. The study aimed to express the metal tolerance and interaction within the microbial abundance in an active non-sanitary landfill soil in Malaysia, as a developmental strategy for selecting bacterial species important for future remediation of metal-polluted soil. The characterized soil exposed the contamination level from heavy metals at the selected active non-sanitary landfill. Further assessment on the microbial community identified and typed the bacterial diversity in the contaminated area. Exposure to varying metal solutions showed the sensitivity of the bacteria species. Microbiological media infused with Pb, Al and Mn solutions demonstrated absolute heavy growth for all the six microbes studied at metal concentrations of 5–20 ppm. Comparison between the microbes indicates that Burkholderia vietnaminesis expressed higher metal resistance. In general all the isolated microbes demonstrated the ability to tolerate and resist metals at different concentrations. Bacterial isolates, mainly the gram-positives are metal-specific and may act as potential agent for remediation of heavy metal in contaminated sites. Graphical abstract: Highlights: Some bacteria species of non-sanitary landfill soil are chemolithotrophs. Agar-well diffusion test established significant sensitivity assessment of metal-tolerant microbes. Burkholderia vietnamiensis and Rhodococcus rubber demonstrated absolute resistance that characterize bioremediation agent.